SOSTAC-based promotion strategy for the development of wellness tourism village in Bandung City - Kartika, Ratu Dika; Asyifa, Nurul; Ardian, Ardian (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2025)
Tourism plays a strategic role in economic development, both national and local. In the context of tourism development in villages, community participation is the ideal key, supported by human, natural and cultural resources. The integration of local wisdom in the concept of health tourism in the Tourism Village is expected to increase tourist attraction and support the Ministry of Tourism's goal of creating quality tourism experiences. As one of the sub-districts in Bandung City which is rich in natural and cultural wealth, Cibiru has great potential to be developed as a health tourism destination. The increasing focus on wellness tourism by Indonesia’s Ministry of Health highlights Cibiru’s strong potential in this sector. However, stakeholders have not yet explored this opportunity, particularly in assessing and formulating promotional strategies for wellness tourism development. To harness this potential, a structured marketing framework is essential to align promotional efforts with strategic objectives. This study employs a qualitative survey approach, conducting interviews with the Tourism Office (Dinas Pariwisata), POKDARWIS, MSMEs, farmers, and cattlemen to explore social phenomena and identify the current situation in Cibiru. To formulate effective solutions, the SOSTAC framework was applied, emphasizing situational analysis, goal setting, strategy and tactic development, role assignment, and activity evaluation. The study concludes that integrating Cibiru’s tourism potential with the wellness tourism concept can help establish a destination that is not only attractive but also provides visitors with a holistic health experience.